2021
DOI: 10.3390/medicina57070653
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines and Arterial Stiffness in Obesity

Abstract: Adipokines are active molecules with pleiotropic effects produced by adipose tissue and involved in obesity-related metabolic and cardiovascular diseases. Arterial stiffness, which is a consequence of arteriosclerosis, has been shown to be an independent predictor of cardiovascular morbidity and mortality. The pathogenesis of arterial stiffness is complex but incompletely understood. Adipokines dysregulation may induce, by various mechanisms, vascular inflammation, endothelial dysfunction, and vascular remodel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 205 publications
(246 reference statements)
2
22
0
2
Order By: Relevance
“…Previous studies have proved the correlation between obesity and arteriosclerosis. 18 19 Studies by Tang et al 8 and Vianna et al 9 demonstrated a positive correlation between BMI and baPWV, while studies by Rodrigues et al, 10 a Brazilian scholar, and Yang et al , 11 a Chinese scholar, advocated that BMI was negatively correlated with baPWV. Their results are apparently contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have proved the correlation between obesity and arteriosclerosis. 18 19 Studies by Tang et al 8 and Vianna et al 9 demonstrated a positive correlation between BMI and baPWV, while studies by Rodrigues et al, 10 a Brazilian scholar, and Yang et al , 11 a Chinese scholar, advocated that BMI was negatively correlated with baPWV. Their results are apparently contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that hypoadiponectinemia is associated with obesity, insulin resistance, cardiovascular disease, dyslipidemia, hypertension, and metabolic syndrome [25]. In addition, adiponectin has antiatherogenic properties, as shown by its capacity to inhibit monocyte adhesion to endothelial cells and macrophage-tofoam cell transformation [26]. There are a limited number of studies investigating the association between alteration of adiponectin levels and AED usage.…”
Section: Discussionmentioning
confidence: 99%
“…Pro-inflammatory cytokines increase leptin synthesis and release, contributing to chronic inflammation in obesity. Obesity-induced hyperleptinemia stimulates the production of pro-inflammatory cytokines such as TNF-α, IL-6, IL-2, IL-1β, and interferon-γ (IFN-γ) by monocytes and T-helper 1, and also inhibits the production of the anti-inflammatory cytokine IL-4 [ 35 , 36 ]. Inflammation disrupts the signaling pathways triggered by leptin and contributes to the development of leptin resistance.…”
Section: Pro-inflammatory Adipokines In Obesity and Its Complicationsmentioning
confidence: 99%